2014
DOI: 10.1159/000366350
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Depletion Attenuates Isoproterenol-Induced Hypertrophy and Endoplasmic Reticulum Stress in Cardiomyocytes

Abstract: Background/Aim: Polyamines (putrescine, spermidine and spermine) play an essential role in cell growth, differentiation and apoptosis. Hypertrophy is accompanied by an increase in polyamine synthesis and endoplasmic reticulum stress (ERS) in cardiomyocytes. The present study was undertaken to elucidate the molecular interactions between polyamines, ERS and cardiac hypertrophy. Methods: Myocardial hypertrophy was simulated by incubating cultured neonatal rat cardiomyocytes in 100 nM isoproterenol (ISO). Polyami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…Consistently with previous studies, we also observed myocardial hypertrophy induced by ISO [10]. ISO is able to induce an increase of the surface area of cardiomyocytes and mRNA expression of ANP compared with the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently with previous studies, we also observed myocardial hypertrophy induced by ISO [10]. ISO is able to induce an increase of the surface area of cardiomyocytes and mRNA expression of ANP compared with the control group.…”
Section: Discussionsupporting
confidence: 92%
“…Primary cultures of neonatal rat cardiomyocytes were performed just as previously described [10,11]. Neonatal rat cardiomyocytes were prepared from 2-3 day old neonatal Wister rats.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…The method of quantifying the level of gene expression was as previously described [10,11]. The RNA was reverse transcribed with oligo-dT and Superscript First-strand Synthesis System for RT-PCR (TaKaRa), The cDNA was then amplified using an iCycler (ABI) and the Brilliant SYBR Green QPCR master mix (TaKaRa) withβ-actin as an internal control.…”
Section: Real Time-pcr Analysismentioning
confidence: 99%
“…Although initially compensatory, prolonged cardiac hypertrophy frequently leads to cardiac dysfunction, heart failure, and even sudden death [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%